2024
DOI: 10.1021/acs.jpcc.3c08236
|View full text |Cite
|
Sign up to set email alerts
|

Novel One-Dimensional Organic–Inorganic Hybrid Halide Perovskite Material with Coexistence of High Phase Transition Temperature and Corresponding Dielectric Response

Yinan Zhang,
Zhuoer Cai,
Xiu-Ni Hua
et al.

Abstract: Organic−inorganic hybrid perovskite materials have attracted much attention because they combine the advantages of the organic and inorganic components at the molecular level. Organic−inorganic hybrid materials have both the structural variability and the flexibility of organic components, as well as magnetic, electrical, and thermal properties of inorganic components. A novel one-dimensional organic−inorganic hybrid halide perovskite material [Et 3 NCH 2 Br][PbBr 3 ] (compound 1) undergoes a high-temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
0
0
Order By: Relevance
“…It may be due to the increase in the distance between the anionic backbones from the one-dimensional chain structure ( 1 ) to the zero-dimensional structure ( 2 ), so the bandgap value decreases from 3.31 to 2.26 eV. Zhang et al found in their study that the bandgap value gradually decreases as the sizes of the cations increase for fixed anions. , With the introduction of F and COOH, the cations become larger, and the bandgap value decreases, which is consistent with the above reports. This finding is of great significance for the design of novel materials with specific electronic properties, especially in the research and development of materials in the fields of semiconductors, optoelectronic devices, and energy storage, where the bandgap value can be optimized by precisely regulating the cation size to enhance the material properties, and technological progress.…”
Section: Resultssupporting
confidence: 76%
“…It may be due to the increase in the distance between the anionic backbones from the one-dimensional chain structure ( 1 ) to the zero-dimensional structure ( 2 ), so the bandgap value decreases from 3.31 to 2.26 eV. Zhang et al found in their study that the bandgap value gradually decreases as the sizes of the cations increase for fixed anions. , With the introduction of F and COOH, the cations become larger, and the bandgap value decreases, which is consistent with the above reports. This finding is of great significance for the design of novel materials with specific electronic properties, especially in the research and development of materials in the fields of semiconductors, optoelectronic devices, and energy storage, where the bandgap value can be optimized by precisely regulating the cation size to enhance the material properties, and technological progress.…”
Section: Resultssupporting
confidence: 76%
“…Such arrangement enables cations to have greater freedom of dynamic movement. 26,28 And each trans -4-methylcyclohexylammonium cation is bound to the adjacent two inorganic chains through N–H⋯Cl hydrogen bonding interactions with the average donor–acceptor distance of about 3.31 Å, forming two-dimensional hydrogen-bonded networks along ab -plane (Fig. S2a and b†).…”
Section: Resultsmentioning
confidence: 99%
“…Exploration for materials with high-temperature phase transition is critical for advancing the field of hybrid perovskites, which has a direct bearing on the effectiveness of the material in harsh working conditions and holds great promise for applications in electronic and optoelectronic devices, particularly in the realm of switches and memories. 21–23 Despite the extensive array of efforts directed towards manipulating phase transition temperatures through strategies such as halogen substitution, modulation of intermolecular interactions, and engineering of void occupancy, 24–28 reports on hybrid perovskite phase transition materials that capitalize on the synergistic effects of symmetry breaking and unconventional configuration changes are notably scarce. In recent studies focused on phase transition hybrid crystals, it has been discovered that certain organic cations with adaptable cis / trans -configurations can serve as unique components.…”
Section: Introductionmentioning
confidence: 99%